Changes in Uterine Glandular Composition in Kyrgyz Breed Mares According to Pregnancy Status - Risvanli, Ali; Salykov, Ruslan; Timurkaan, Necati; Seker, Ibrahim; Ekinci, Elif (Wiley, 2025)
This study was conducted to examine glandular histological changes in the uterus of Kyrgyz breed mares during the first 6 months of pregnancy. The study used 53 Kyrgyz breed mares; 43 of these were at different stages of pregnancy, while 10 were non-pregnant mares. Uterine samples obtained at the slaughterhouse were evaluated histomorphometrically; endometrial thickness, gland density, gland epithelial height and gland diameter were measured. In conclusion, it was concluded that in Kyrgyz mares, endometrial thickness, glandular epithelial height and diameter increased as pregnancy progressed, while glandular density decreased and that further research on this topic would be beneficial.
Keywords: gland; histology; Kyrgyz; mare; pregnancy; uterus